TINDAK TUTUR PERLOKUSI GURU DALAM PEMBELAJARAN BAHASA INDONESIA KELAS XI SMK NEGERI 1 SAWIT BOYOLALI - Insani, Eka Nur; Sabardila, Atiqa (Jurnal Penelitian Humaniora, 2016)
This study reviews the perlocution speech acts of Indonesian language teachers in class XI SMK 1 Sawit, Boyolali. This research aims to describe the classification of perlocution speech acts in Indonesian language teachers in class XI SMK Negeri 1Sawit, Boyolali and to describe its functions. This research used descriptive qualitative methods. The analyses techniques used in this research refer to free skilled, technical notes, and recording. The results showed that there are four types of perlocutionspeech acts. They are directive-perlocution speech act, expressive-perlocution speech act, representative-perlocution speech acts and commissive-perlocution speech acts. The directive-perlocution speech acts were found in the forms of orders, reservationsand giving advice. The expressive perlocution speech acts involves hatred, pleasure, excitement. The representative form of speech acts include affirmation, description, statement of facts and conclusions. The commissive form of speech acts include denial. The results of this research showed that the perlocution speech acts function found in Indonesian language teachers are the functions for competitiveness and fun.